Dispute Resolution of Akad Mudharabah Muqayyadah (Analysis of Decision No. 1695/Pdt.G/2012/PA. Js, Number 5/Pdt.G/2014/PTA. Jk and Number 272 K/Ag/2015) - Fauzi, Muhammad Yasir; Pane, Erina; Hasan, Muhamad (Universitas Islam Negeri Raden Intan Lampung, 2023)
Sharia economic dispute resolution in Indonesia can be resolved through litigation and non-litigation. Through litigation becomes the absolute authority of religious courts, while non-litigation can be through deliberation, mediation or sharia arbitration bodies. The problem in this study is about the disparity in the decision of religious court judges in deciding disputes over mudharabah muqayyadah contracts submitted in religious courts, namely Decision Number 1695 / Pdt.G / 2012 / PA. Js, Number 5/Pdt.G/2014/PTA. Jk and Number 272 K / Ag / 2015, which in its contract mentions the sharia arbitration body as a dispute resolution institution. The purpose of this study is to analyze the judge's consideration of the disparity of the three rulings. This type of research is literature research and the nature of analytical descriptive research. The data obtained was sourced from the document of the South Jakarta Religious Court Decision Number 1695 / Pdt.G / 2012 / PA. Js, Jakarta High Religious Court Decision Number 5/Pdt.G/2014/PTA. Jk and Supreme Court Decision Number 272 K / Ag / 2015. Data collection techniques by means of library and documentation methods. Data analysis using qualitative analysis research methods. The results of this study showed that the South Jakarta Court Decision granted the Plaintiff's lawsuit by not considering the authority of the religious court in resolving the dispute despite the difference in contract clauses, the Jakarta High Religious Court stated that the religious court was not authorized to adjudicate the dispute because there was an arbitration clause in the contract, while the Supreme Court ruled that the religious court was authorized to resolve the dispute with consideration under Article 1343 and Article 1344 of the Civil Code, that is, the will of the parties takes precedence.Keywords: contract mudharabah muqayyadah, sharia economics, dispute resolution